Effect of Corn Distiller`s Dried Grains with Solubles at Various Levels on Performance of Laying Hens and Egg Yolk Color - Roberson, K.D.; Kalbfleisch, J.L.; Pan, W.; Charbeneau, R.A. (International Journal of Poultry Science, 2005)
Distiller`s dried grains with solubles produced from corn as a co-product from ethanol production was fed at 0, 5, 10, or 15% of a corn-soybean meal diet to laying hens to determine if egg production parameters or yolk color would be affected. In experiment 1, diets were fed from 48 to 56 wk of age and DDGS had a goldenrod color. Egg production, weight, mass, specific gravity and yolk color were determined biweekly. Brown colored DDGS was included in diets fed from 58 to 67 wk of age. Egg production parameters and yolk color were measured tri-weekly. Egg production parameters were not different at most ages. However, there were occasional treatment effects. As DDGS increased, there were linear decreases in egg production (52-53 wk of age), egg weight (63 wk of age), egg mass (51 and 53 wk of age), and specific gravity (51 wk of age). Yolk color was increased linearly (p